Pharmacoeconomic feasibility of using Mirabegron in patients with overactive bladder - I. N. Dyakov; G. R. Kasyan (Izdatelstvo OKI, 2021)
Objective: to assess the clinical and economic efficiency and impact on the budget when using the drug Mirabegron in the treatment of an overactive bladder. Materials and methods. Study design - retrospective analysis of published data. Pharmacoeconomic analysis methods - cost analysis, clinical and economic analysis, budget impact analysis. Results. Despite the fact that the drug Mirabegron for the treatment of overactive bladder is less effective in comparison with the use of the botulinum toxin type A-hemagglutinin complex drug, the clinical and economic analysis showed that within the horizon of 12 months the use of the drug Mirabegron will require 66.8 % less costs. Analysis of the impact on the budget showed that when using the drug Mirabegron from the first year in 100 % of patients, the decrease in the burden on the budget will be 66.8 %. Gradual provision of Mirabegron to patients over 3 years instead of Botulinum toxin type A-hemagglutinin complex will reduce the burden on the budget by 44.4 % in 3 years. Sensitivity analysis showed that the results obtained are resistant to changes in prices for compared drugs and a decrease in the volume of therapy with botulinum toxin type A-hemagglutinin complex. Conclusion. The use of the drug Mirabegron in the treatment of patients with an overactive bladder is pharmacoeconomically justified. The inclusion of Mirabegron in the lists of medicines, the costs of which are subject to state reimbursement, is advisable.